The effect of assessment for learning on pre-service mathematics teachers’ higher-order thinking skills in algebra - Ayanaw Yigletu; Kassa Michael; Mulugeta Atnafu (Journal of Pedagogical Research, 2023)
In teacher education, enhancing pre-service teachers' higher-order thinking skills (HOTs) is very crucial. The effect of comprehensive professional development in assessment for learning (AfL) on pre-service teachers' HOTs in an algebra course was investigated using a nonequivalent group quasi-experimental design. A total of 129 pre-service teachers who took the Fundamental Concepts of Algebra course from three different teacher education colleges [TECs] selected randomly from ten Ethiopian TECs, participated in the study. Among these students who attended the course, a group of 52 pre-service teachers with three mathematics teacher educators who gave them the course engaged in comprehensive training and professional development on AfL, while the remaining pre-service teachers were attending the course the usual way in two different TEC. A one-way ANOVA was used to determine whether there was a mean difference among the three groups and three achiever levels on their HOTs scores. The result showed that there is a statistically significant mean difference in the HOTs scores between pre-service teachers in the treatment group and the comparison groups. The results also showed that there was a statistically significant mean difference among the three achiever levels (low, medium, and high) in their HOTs scores in the treatment group before the intervention, but there was no statistically significant mean difference after the intervention. The implications of the results and recommendations are discussed.